Head shape determination and cranial evaluation using anatomical landmarks in children with sickle cell disease (SCD) - Musa, MA; Zagga, AD; Musa, K; Danfulani, M; Ahmed, H (Asian Journal of Medical Sciences, 2014)
Background: Sickle cell disease is one of the commonest diseases widespread in sub-Saharan Africa and Nigeria in particular. This study investigated the possible effects of sickle cell disease (SCD) on the cranial index and pattern of head shapes of children with sickle cell disease in comparison with that of children without SCD. Methods: The head length, head width of 103 children (54 males and 49 females) with sickle cell disease and 218 normal growing non-sickle cell disease children (121 males and 97 females) aged 0-18 years old were measured and their cranial indices calculated. Results: The mean CI for normal growing non sickle cell disease children was 79.82±3.35 and that of the sickle cell disease children was 80.12±3.39 which was not statistically signifi cant (p=0.4526). However, the difference between the mean CI of males in both groups was not signifi cant (p=0.9535) likewise in females (p=0.3127). The mean head circumference in sickle cell disease children was 48.89±3.15 as against that of the normal growing non-sickle cell disease children 44.97±6.07 and this difference was also not statistically signifi cant (p=>0.05). Conclusion: The head shapes as per the present study could be classifi ed as mesocephalic in normal growing non-sickle cell disease children and brachycephalic in sickle cell disease children. Thus, it has been deduced that sickle cell disease could probably have an effect on head length, head width, cranial index and head circumference of affected children. DOI: http://dx.doi.org/10.3126/ajms.v6i1.9160 Asian Journal of Medical Sciences Vol.6(1) 2015 98-102